ENHANCING PRIMARY EDUCATION WITH VIRTUAL REALITY: CHALLENGES AND OPPORTUNITIES - Cristina Mihaela ZANFIR (Association of Social and Educational Innovation, 2023)
This theoretical review aims to explore the considerable potential of Virtual Reality (VR) in primary education, with a specific focus on its transformative impact on early learning. The aim is to conduct an in-depth analysis of the challenges faced in primary education and the role of VR technology in addressing these challenges. By examining the educational landscape, this paper seeks to elucidate how VR technology can substantially enhance the learning experience for young students. Through a meticulous evaluation of the theoretical framework and existing literature, it underscores the promising opportunities and complexities that arise from the integration of VR in primary education. This review primarily serves as a foundational resource for educators, researchers, and policymakers interested in leveraging VR's capabilities to enhance the educational journey of digital-native primary school students.